Spiritualità del monachesimo maschile nelle opere di san Girolamo (Duchowość monastycyzmu męskiego w dziełach świętego Hieronima) - Degórski, Bazyli (Vox Patrum, 2018)
The essay aims at peering into the Monastic writings of St. Jerome expressly addressed to men, though actually to men and women. The works surveyed are mostly St. Jerome’s Letters, though a few homilies held in Bethlehem are taken into consideration, as well as the writing De persecutione Christianorum, a work addressing monks on the release of the Monastic condition. The Monastic teaching of St. Jerome is a vast patrimony, and his authentic personal ascetical lifestyle render him a great master of spirituality. St. Jerome’s Monastic literature does not witness just his own sagacity, but a whole spiritual movement guided by him, which by no means could be assimilated to the Eastern Tradition nor to the Western Benedictine Monasticism, developed later on. His spiritual movement was distinct from the former because of its cultural impact, and from the latter because of its austerity of life, entirely moulid by the desert Fathers. The spiritual movement guided by St. Jerome it’s a peculiar Monasticism, bridging Eastern Monasticism in the West, and still leaving echoes in the present.